Cutting ceramic by turning of nickel alloy Inconel - Mrkvica, Ivan; Neslušan, Miroslav; Konderla, Ryszard; Janoš, Miroslav (Manufacturing Technology Journal, 2012)
This article deals with dry turning of nickel superalloy - Inconel 718. The different ceramic inserts were applied for cutting process. These inserts were produced by Greenleaf Corporation company. This paper discusses durability of cutting inserts, the different intensity of tool wear at various cutting parameters. The most suitable cutting conditions are chosen in the scope of applied tools.
Keywords: turning; Inconel; cutting ceramic; tool wear; dry machining